2017
DOI: 10.1111/cpr.12341
|View full text |Cite
|
Sign up to set email alerts
|

miR‐506 enhances the sensitivity of human colorectal cancer cells to oxaliplatin by suppressing MDR1/P‐gp expression

Abstract: Taken together, the findings of our study demonstrate that miR-506 overexpression in HCT116-OxR cells enhances oxaliplatin sensitivity by inhibiting MDR1/P-gp expression via down-regulation of the Wnt/β-catenin pathway and thus provide a rationale for the development of miRNA-based strategies to reverse oxaliplatin resistance in CRC cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
60
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(63 citation statements)
references
References 31 publications
1
60
0
Order By: Relevance
“…Besse et al () found that MDR1 overexpression was the most important change in carfilzomib‐resistant multiple myeloma cells. Moreover, many studies proved that there was positive relationship between MDR1 and the resistance to various drugs in CC treatment, such as doxorubicin (Du et al, ; Yan, Zhao, & Zhang, ), oxaliplatin (Zhou et al, ), and irinotecan (Paule et al, ). In this study, qPCR data further demonstrated that FOXO3 overexpression had little effects on the expression of other five members of ATP‐binding cassette family in HCT116 cells, including ABCB2, ABCA1, ABCA2, ABCG1, and ABCG2 (Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…Besse et al () found that MDR1 overexpression was the most important change in carfilzomib‐resistant multiple myeloma cells. Moreover, many studies proved that there was positive relationship between MDR1 and the resistance to various drugs in CC treatment, such as doxorubicin (Du et al, ; Yan, Zhao, & Zhang, ), oxaliplatin (Zhou et al, ), and irinotecan (Paule et al, ). In this study, qPCR data further demonstrated that FOXO3 overexpression had little effects on the expression of other five members of ATP‐binding cassette family in HCT116 cells, including ABCB2, ABCA1, ABCA2, ABCG1, and ABCG2 (Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Zhou et al demonstrated that miR‐506 overexpression increases oxaliplatin sensitivity in oxaliplatin‐resistant CRC cells by inhibiting P‐gp expression via downregulation of the Wnt/β‐catenin signaling. They suggested that miR‐506 could be used to develop miRNAs‐based strategies to reduce oxaliplatin resistance …”
Section: Micrornas Drug Accumulation and Oxaliplatin Resistancementioning
confidence: 99%
“…It has been shown that overexpression of miR‐506 downregulates Wnt/β‐catenin signaling pathway and enhances oxaliplatin sensitivity. In addition downregulation of Wnt/β‐catenin signaling pathway by miR‐506 caused inhibiting of the expression of two common drug resistance proteins including multidrug resistance‐associated protein 1 (MRP1) and permeability‐glycoprotein (P‐gp) . Similarly, miR‐204‐5p enhances the chemotherapeutic sensitivity but through downregulation of RAB22A (a member of the RAS oncogene family) …”
Section: Micrornas Signaling Pathway Transcription Factors and Oxamentioning
confidence: 99%
See 2 more Smart Citations